2017
DOI: 10.3390/molecules22081382
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Antioxidant, Antienzymatic and Antimicrobial Activities of Volatile Molecules from Spanish Salvia lavandulifolia (Vahl) Essential Oils

Abstract: The current study describes the composition of Salvia lavandulifolia (Vahl) essential oils (SlEOs) obtained from plants cultivated in Murcia (Spain), as determined by gas chromatography. Relative and absolute concentrations, the enantiomeric ratios of chiral compounds and the in vitro antioxidant, antienzymatic and antimicrobial activities are described. The main components of the SlEOs were camphor, 1,8-cineole, camphene and α-pinene, and the main enantiomers were (+)-camphor and (−)-camphene. The activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 60 publications
1
15
0
Order By: Relevance
“…35 In the present study, we were now reporting that, the role of α-terpinyl acetate and 1,8-cineole showed potentially more effective against microbes as compared to less content originating varieties of α-terpinyl acetate and 1,8‐cineole. 36,37…”
Section: Discussionmentioning
confidence: 99%
“…35 In the present study, we were now reporting that, the role of α-terpinyl acetate and 1,8-cineole showed potentially more effective against microbes as compared to less content originating varieties of α-terpinyl acetate and 1,8‐cineole. 36,37…”
Section: Discussionmentioning
confidence: 99%
“…Kennedy et al [ 36 ] and Temel et al [ 37 ], indicated that S. lavandulaefolia and S. pseudeuphratica EOs were highly potent inhibitor of AChE, with an IC 50 value of 3 and 26.00 μg/mL, respectively. The inhibitory potency of S. lavandulaefolia , collected in different bioclimatic zone in the south-east of Spain, was also investigated by Cutillas et al [ 38 ]. IC 50 ranging from 108.0 to 142.4 mg/L were obtained against AChE.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant character of (AJ) EO may be attributed to the presence of a high percentage of bornyl acetate which also showed potential antioxidant activity in several published works and approved that it has the potentials to scavenge free radicals and reduce oxidative stress [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present investigation revealed that (AJ) EO has potent antibacterial and antifungal potentials against certain strains of microbial species. Actually, bornyl acetate, the study’s main molecule, has long been recognized as a potent antimicrobial agent, according to numerous published studies [ 36 , 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%